Optimizing learning & teaching on paediatric ward rounds - Mantzor, Savarra (Department of Health Sciences Education, 2024)
Bandura's Social Cognitive Theory asserts that an individual's perceptions of his/her self-efficacy influence not only their ability to learn knowledge and skill, but more importantly, influences their ability to act utilizing that knowledge or skill. In the context of health professional education, it is not enough to know the facts of medicine, but learners must also have a positive perception of their selfefficacy in order to practice medicine as a competent physician. The aim of this study was to improve the quality of ward round learning and teaching for University of Botswana medical trainees working in the Department of Paediatrics at Princess Maria Hospital in order to enhance their self-efficacy beliefs regarding their ability to provide paediatric patient care. Specifically, we utilized a threepronged approach to 1) improve trainees' participation in, and sense of belonging to, a local community of clinical practice, 2) introduce a structured bedside teaching model, and 3) promote a favourable clinical learning environment, all of which we postulated could improve trainees' selfefficacy beliefs. In this research I assert that four educational elements, (i) the method of teaching (i.e. bedside teaching), (ii) the environment in which learning occurs (i.e. the clinical learning environment), (iii) the epistemological value of social participation (i.e. communities of practice), and (iv) an individual's ability to both acquire and utilize their knowledge (i.e. perceived self-efficacy), are not distinct phenomena, but are interrelated, dynamic forces that influence each other in meaningful ways. This study was conducted as an action research (AR) project using mixed methods evaluation for data capture and analysis. Following the iterative Plan-Act-Observe-Reflect cycles of action research, a total of three phases occurred. In Phase 1, we developed an in-depth understanding of trainees' and faculty's perceptions of the prevailing paediatric ward rounds. In Phase 2, through ongoing departmental collaboration and review of the literature, we conceptually analysed the findings from Phase 1 to determine specific interventions for Phase 3. In Phase 3, we implemented the Phase 2 generated solutions, including the introduction of a structured bedside teaching model, SNAPPS (Summarize-Narrow-Analyse-Probe-Plan-Select); this was subsequently adapted to provide local and contextual relevance. Throughout all Phases, we conducted serial measurements of trainees' perceptions of (i) the clinical learning environment (CLE) on ward rounds, (ii) their sense of participation in, and belonging to, the community of practice on ward rounds (COP); and (iii) their perceived self-efficacy (PSE) to provide paediatric patient care. The types of study instruments and data sources included focus group discussions, interviews, debriefs, my action research journal, and questionnaires. Four consecutive types of data analysis occurred throughout the project: qualitative data analysis, quantitative data analysis, mixed methods integration, and critical reflection. Over the 28-month study period, there was a total of 208 participants, including representation from faculty, senior residents, junior residents, and medical students. There were three primary outcomes of this action research project. 1) Trainee use of SNAPPS was associated with (i) a CLE that was more favourable to respecting uncertainty; (ii) an increase in trainees' participation in and, sense of belonging to, a paediatric ward round; and (iii) positive influences on their perceived self-efficacy to manage patients. 2) We identified several non-traditional uses of SNAPPS that created opportunities for trainees to learn and faculty to teach beyond the primary diagnosis. 3) In contrast to the literature, we were unsuccessful at introducing SNAPPS at a department-wide level. Note, when I first set out to do this research, I postulated that bedside teaching, the clinical learning environment, and participation in a community of practice all had the potential to influence an individual's perceived self-efficacy. I assumed that while bedside teaching models (BTM) provide a structured approach to student engagement to enhance the content of bedside teaching, they do not, in and of themselves, regulate the clinical learning environment in which they occur. I did not consider the influence of a BTM on a learner's sense of belonging to a community of clinical practice. Through the findings of this project, I discovered the power of the BTM itself, which shifted the foci of influence, that not only does it have the potential to positively influence learner's PSE, but indeed has direct influential effects on the CLE and elements of COP. These findings compliment and broaden my original assumptions that the educational dimensions involved are not isolated elements, but together simultaneously impact learning and teaching. Note, during the course of this project, my positionality as the researcher underwent considerable shifts from “outsider” conducting “participatory action research” to “insider” conducting “practitioner research”. In turn, an unexpected secondary aim and outcome developed – to explore, understand and articulate the influences of SNAPPS on my own practice as a physician and clinical teacher. Limitations included: over utilization of traditional research instruments and analysis; lack of quality control of the implemented intervention; difficulty in interpreting results; delays in important critical reflections during the project; inability to achieve full collaboration with other department members; and unsuccessful attempt to introduce SNAPPS department-wide. Based on the findings from this study, a structured bedside teaching model, specifically SNAPPS, offers a holistic approach to maximize learning and teaching, addressing several learner and environmental needs concurrently. That said, when clinical teachers set out to introduce SNAPPS, they ought to be prepared to offer ongoing support for the successful implementation beyond a brief SNAPPS sensitization. The flexibility and potential advantages of SNAPPS promotes its use, especially in clinically challenging teaching environments.